EFFECT OF DIFFERENT TREATMENT ON QUALITY SENSORY AND TRASH FISH CHEMICAL RAW MATERIALS AS FISH MEAL - Wahid, Nur; Hasan, Bustari; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aim of this study was to evaluate the effect of boiling, salting andicing effectivity in maintaining the chemical and sensory quality of the trashedfish flour. The experimental design used was a randomized block design (RAK)with 1 factor. Treatments of the study were boiling, salting and icing whichconsists by 3 stages, suchas: first stage; fish was boiled into boiling water for 15minutes, second stage; fish was salted with salt 15%, and third stage; fish was icedwith comparation 2: 1 of ice and fish on temperature 5â„ƒ. The time of storage oftrashed fish was group (4, 6, 8, and 10 days). The parameters was were sensoricvalue (odor), proximate composition, NPN and TVB. The results showed thesensoric value of the trashed fish wich was boiled and iced for storage bad odorand had been rejected on 6 day. Although, the trashed fish wich was salted hadno bad odor and still received for storage. The average value of sensoric quality ofthe trashed fish was boiling 7,63, salting 7,83 and 4,96 icing. For chemicalanalysis (proximat value, NPN and TVB), the best treatment of the trashed fishwith boiling treatment. The proximat compotition of the salted trashed fish forstorage were water value 8,28%, ash value 25,84% , fat value 7,01% and proteinvalue 51,87%. While the value of NPN and TVB were NPN 0,28% and TVB5,41mg.Keywords: Trashed fish, fish flour, boiling, salting and icing.